Reduction in ribonucleotide reductase subunit RRM2 associated with alterations in mitochondrial proteins, leading to impaired gut health of woody breast chicken - Shakeri, Majid; Ziabtchenko, Elizabeth; Harris, Caitlin; Choi, Janghan; Naeini, Hamid Reza Rafieian; Kim, Woo Kyun; Kong, Byungwhi; Bowker, Brian (Frontiers in Animal Science, 2025)
The woody breast (WB) condition impairs the quality of chicken breast meat, causing a financial loss for the poultry industry. Recent studies suggest that the mitochondria may play a role in muscle and gut health by regulating inflammatory mediators. However, there is limited information available on gut and pancreas health as they relate to WB. Ribonucleotide reductase (RNR), subunit RRM2, is involved in DNA synthesis and mitochondrial function. Inhibition of RRM2 increases gastrointestinal disturbances and apoptosis in the pancreas by disturbing inflammatory mediators and mitochondrial homeostasis. This study aimed to investigate the links between RRM2, pancreas, and gut health in broilers exhibiting WB. Sixty eight-week-old male broilers were used to collect breast muscle, duodenum, and pancreas from 10 broilers exhibiting severe WB and 10 normal (N). Gene expression was measured using qRT-PCR with SYBR reagents. Commercial biochemical assays were used to measure mitochondrial function. To determine if RNR controls mitochondrial functions, an RNR inhibitor was tested in vitro on avian muscle-derived cells. Data were analyzed using Prism and t-tests. In tissues, RRM2 expression was lower in the muscle (P = 0.03), pancreas, and duodenum (both P = 0.04) vs. N. The expression levels of cytochrome b (Cytb) and mitochondrial uncoupling protein 3 (UCP3) were reduced in the muscle (P = 0.05 and P = 0.002) and pancreas (P = 0.009 and P = 0.002) for WB, while only Cytb was reduced in the duodenum (P = 0.04). Total mitochondrial protein and mitochondrial complex V activity were reduced for WB in the muscle (P = 0.0006 and P = 0.004), pancreas (P = 0.01 and P = 0.002), and duodenum (P = 0.001 and P = 0.002), respectively. Broilers with WB had increased malondialdehyde only in the pancreas (P = 0.01). Reduced GSH/GSSG ratios in the muscle (P = 0.01), pancreas (P < 0.05), and duodenum (P = 0.01) of WB broilers indicate more reactive oxygen species (ROS) in the tissues. In vitro, cells treated with an RNR inhibitor had reduced expression of RRM2 (P < 0.0001), Cytb (P = 0.0006), and UCP3 (P = 0.002) as well as reduced mitochondrial complex V activity (P = 0.001) and total mitochondrial proteins (P = 0.01), indicating that RNR may regulate mitochondrial functions. In conclusion, reduced RRM2 expression may potentially reduce RNR function in the muscle, duodenum, and pancreas of broilers with WB and alter tissue function by increasing ROS production, mitochondrial abnormalities, and oxidative damage while reducing energy production.